Solid Fuels Technology and Applications. - Koukouzas, Nikolaos; Tyrologou, Pavlos; Koutsovitis, Petros (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue presents the latest state-of-the-art research on solid fuels technology with dedicated, focused research papers. There are a variety of topics to choose from among the seven published re-search works to bring you up to date with the current trends in academia and industry.